Diskresi Peradilan dalam Penyelesaian Perkara Warisan: Menuju Keadilan Hukum Progresif di Indonesia - Zaidah, Yusna (Syariah: Jurnal Hukum dan Pemikiran, 2024)
The results of the creativity of judges in conducting legal discovery with various methods allow for decisions that contain legal discretion in order to realize progressive legal justice. The presence of discretion to correct all weaknesses, independence is very important in the aspect of legal sources. Through in-depth research using normative legal studies on several decisions of the Religious Courts in South Kalimantan, it was found that a form of free discretion was found when the judge in the purification of the inheritance gave part of the inheritance through the establishment of a mandatory will for the ex-wife and justified the use of the inheritance for the payment of the spirit ritual debt. Such discretion of judges is categorized as ideal discretion because it is very progressive, where judges not only use normative interpretation but rather use sociological interpretation and connect the law with humanity, and morality.